The persistence and uniqueness of fingerprints (Academic Journal of Internal Affairs, 2016)
The authors provide an overview of the forensic application of uniqueness and persistence of fingerprints, from the embryonal development through the structure of skin texture.
Keywords: fingerprint; analysis; forensic application